Assessing the abundance of fungal populations in a full-scale membrane bioreactor (MBR) treating urban wastewater by using quantitative PCR (qPCR). (1st October 2018) - Maza-Márquez, P.; Vílchez-Vargas, R.; González-Martínez, A.; González-López, J.; Rodelas, B.
Abstract: The abundance of fungi in a full-scale membrane bioreactor (MBR) treating urban wastewater and experiencing seasonal foaming was assessed by quantitative PCR (qPCR), comparing three different sets of widely used universal fungal primers targeting the gene encoding the small ribosomal subunit RNA, 18S-rDNA, (primers NS1-Fung and FungiQuant) or the internal transcribed spacer ITS2 (primers ITS3-ITS4). Fungi were a numerically important fraction of the MBR microbiota (≥10 6 18S-rDNA copies/L activated sludge), and occurred both in the aerated and anoxic bioreactors. The numbers of copies of fungal markers/L activated sludge calculated using the NS1-Fung or ITS3-ITS4 primer sets were up to 2 orders of magnitude higher than the quantifications based on the FungiQuant primers. Fungal 18S-rDNA counts derived from the FungiQuant primers decreased significantly during cold seasons, concurring with foaming episodes in the MBR. Redundancy analysis corroborated that temperature was the main factor driving fungi abundance, which was also favored by longer solid retention time (SRT), lower chemical oxygen demand/biochemical oxygen demand at 5 days (COD/BOD5 ) of influent water, and lower biomass accumulation in the MBR. Graphical abstract: Highlights: Abundance of total fungal populations was evaluated in a MBR by qPCR. Three different primers sets were compared for fungal quantification. Fungi were a numerically important fraction of the MBR microbiota. Temperature was the main factor influencing fungi abundance in the MBR.